Kinematic and kinetic tumbling take-off comparisons of a spring-floor and an air floor(TM): a pilot study - Sands, W. A.; Kimmel, W. L.; McNeal, J. R.; Smith, S. L.; Penitente, G.; Murray, S. R.; Sato, K.; Mizuguchi, S.; Stone, M. H. (Science of Gymnastics Journal, 2013)
Tumbling take-offs on floor exercise apparatuses of varying stiffness properties may contribute to apparatus behaviors that lead to increased injury exposure. The purpose of this pilot study was to compare the kinematics, kinetics, and timing performance characteristics of a spring-floor and a spring-floor with an added Air FloorTM. Five male international gymnasts performed a forward handspring to forward somersault and a round off, flic flac, backward somersault on a standard spring-floor and a spring-floor with an Air FloorTM. Performances were measured via high-speed video kinematics (lower extremity joint angles and positions), electromyography of eight lower extremity muscles, mean peak forces on the feet, and timing. Comparisons of spring-floor types, lower extremity joint angles, lower extremity muscle activations, foot forces, and selected durations were determined. The spring floor with Air FloorTM resulted in longer take-off contact durations than spring-floor alone. Dynamic knee angles may indicate an unexpected and potentially injurious motion of the triceps surae musculotendinous structures. This pilot and hypothesis generating study has suggested future research examining dynamic knee position and angle changes, the role of spring-floor vibration and stiffness in take-offs, and take-off muscle activation alignment with the stiffness of the spring-floor. Pragmatically, there appears to be a convergence of evidence indicating that a slower frequency response of the spring floor may assist tumbling performance and reduce stress and strain in the lower extremity.